2017
DOI: 10.1111/eea.12600
|View full text |Cite
|
Sign up to set email alerts
|

Effect of semiochemicals and trap height on catch of Neocerambyx raddei in Jilin province, China

Abstract: We conducted experiments in Jilin, China, in 2011 and 2014 in forest stands dominated by mature Quercus mongolica Fisch. ex Ledeb. (Fagaceae) to test the effects of longhorn beetle pheromones, plant volatiles, and trap height on catch of Neocerambyx raddei (Blessig & Solsky) (formerly Massicus raddei) (Coleoptera: Cerambycidae) in traps. Traps captured 276 specimens of N. raddei in 2011 and 379 specimens in 2014 (384 females, 271 males). Ethanol was attractive to female but not male N. raddei. However, N. radd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 32 publications
(51 reference statements)
0
7
0
Order By: Relevance
“…Primary among the spatial factors to consider in forest settings is trap location along environmental gradients, specifically horizontal edge–interior and vertical understory–canopy gradients. Although consistent patterns in gradient effects among forest Coleoptera have not yet emerged, it is clear that they have strong impacts on the diversity and abundance of the species captured [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Primary among the spatial factors to consider in forest settings is trap location along environmental gradients, specifically horizontal edge–interior and vertical understory–canopy gradients. Although consistent patterns in gradient effects among forest Coleoptera have not yet emerged, it is clear that they have strong impacts on the diversity and abundance of the species captured [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Tang et al (2016) used the combination of three mitochondrial genes to study the genetic structure of Galerucella birmanica Jacoby (Coleoptera: Chrysomelidae) in its main distributional habitats. Moreover, Javal et al (2017) (Li et al, 2017;Tang, 2011;Wang et al, 2010;Yang et al, 2013Yang et al, , 2014. However, as yet there has been no further researches into genetic aspects of M. raddei populations in China.…”
Section: Introductionmentioning
confidence: 99%
“…(2020) presented the entire genetic structure among ALB ( A. glabripennis ) populations of South Korea and confirmed that ALB invasion has occurred even within the species’ native ranges based on COI mitochondrial sequences. Studies on M. raddei have focused mostly on its biology, damage pattern, field surveys for natural enemies, and integrated control measures (Li et al., 2017; Tang, 2011; Wang et al., 2010; Yang et al., 2013, 2014). However, as yet there has been no further researches into genetic aspects of M. raddei populations in China.…”
Section: Introductionmentioning
confidence: 99%
“…The species and subfamilies with different habits showed different distribution patterns in the canopy and bottom (Ulyshen et al 2019), and different species were distributed in different parts of the forest (Li et al 2017;Flaherty et al 2019;Foit et al 2019). In this study, Massicus raddei (Blessig), Moechotypa diphysis (Pascoe), and Mesosa myopsmyops (Dalman) preferred to be active in the canopy.…”
Section: Spatial Distribution Of the Longhorn Beetle Communitymentioning
confidence: 60%